Morphological analysis of testes from post-hatch chicks submitted to temperature variation during incubation - doi: 10.4025/actascibiolsci.v33i2.8187 - Amaral, Rodrigo de Souza (2011)
This study aimed to evaluate the effects of temperature variation during incubation on testicular morphology of post-hatch chicks. We utilized 60 eggs incubated under different temperatures: Group 1 – 37.5°C; Group 2 – 39.5°C; and Group 3 – 34°C. Chicks were weighted and the testes were histologically analyzed. All eggs from Group 3 showed embryonic death. There were no significant differences in body weight and testicular morphology between Groups 1 and 2; however, there was a difference in the diameter of the seminiferous tubules (p < 0.001). The increase in temperature to 39.5°C during incubation causes a decrease in diameter of the seminiferous tubules.